Business Development in Kuta after COVID-19: Navigating New Challenges and Opportunities - I Kadek Bagiana (Samā Jiva Jnānam (International Journal of Social Studies), 2023)
The COVID-19 pandemic has had a profound impact on global economies, with the tourism and hospitality sector being one of the hardest hit. Kuta, a renowned tourist destination in Bali, Indonesia, experienced significant disruptions to its vibrant business ecosystem. This research journal aims to explore the implications of the pandemic on the business development landscape in Kuta and shed light on the challenges and opportunities that lie ahead. By examining the multifaceted dimensions of business recovery and growth, this study seeks to provide valuable insights for entrepreneurs, policymakers, and stakeholders alike. Through a comprehensive analysis of the post-pandemic scenario, we aim to formulate strategies that can foster sustainable and resilient business development in Kuta.